Efecto del esteroide andriol undecanoato de testosterona en la masculinización de tilapia roja oreochromis sp - Pineda Espinoza, Marcos Jesús (2015)
Tilapia farming on a larger scale in Ecuador started with the appearance of white spot virus, which affected shrimp production, thus allowing a small market (niche) for tilapias in our country, whose exportations abroad have been declining. However there is an increasing interest in the rural community, as fish farming is an alternative that contributes to food security for families, improving their nutritional quality by consuming good quality protein. Tilapia is a fish that reproduces easily and in large numbers in captivity, being sexually mature by age 3 months and repeating it every two months. Females are generally smaller in size while males reach an acceptable market size. Therefore tilapia masculinization is performed to obtain the highest possible percentage of (monosex) male organisms. This research was conducted at the Laboratory of Mariculture, Faculty of Agricultural Sciences, Technical University of Machala, and had the following objectives: 1) To determine the commercial dose of hormone Andriol (undecanoato de testosterona) optimal for an appropriate percentage of masculinization in tilapia, 2) To determine the percentage of survival of fry per treatments, 3) To compare the final weight reached by the fry in the different treatments. The results of this investigation indicate that the percentages of masculinization of tilapia fry undergoing hormone Andriol varied between 58% and 80.30% in the three treatments, with the dose of 90 mg/kg reporting the highest percentage of masculinization. It is also noted that Andriol at a concentration of 30 mg/kg feed a survival rate of 85.3% was obtained, whereas those fed at a concentration of 60 mg/kg a survival percentage of 82.7% was reported. In a similar fashion, adding a higher hormone concentration (90 mg / kg) reported a further decrease in survival rate (78%). With the data here presented, it can be concluded that the observed percentage of masculinization is directly proportional to the concentration of hormone applied. Furthermore, survival rates obtained in this research show that as the dose of hormone increased, this directly affected the survival of organisms under treatment.